Literature Review: Implications of Educational Philosophy for the Theory and Practice of Education in Indonesia - Amri, Huriyah Anisah; Ismail , Ismail (Jurnal Ilmiah Profesi Pendidikan, 2025)
The philosophy of education plays a crucial and fundamental role in determining the direction, goals, and practices of education in Indonesia. The study of educational philosophy encompasses the values, principles, and goals that serve as the primary foundation for the implementation of education. Furthermore, philosophy serves as a normative foundation for formulating national policies and developing curricula relevant to the needs of the times. This study employed a literature review method, examining various sources, including academic books and related scientific journals. The analysis focused on understanding the basic concepts of educational philosophy and its branches, namely ontology, epistemology, and axiology, along with their implications for educational theory and practice in Indonesia. The research findings indicate that educational philosophy provides clear direction in the formulation of learning objectives, teaching methods, curricula, the roles of teachers and students, and evaluation systems. Furthermore, philosophy plays a strategic role in responding to the challenges of globalization and digitalization by maintaining a balance between technological advancement and humanitarian values, so that education remains oriented toward the formation of holistic character.